Employees’ Well-Being during the COVID-19 Pandemic: Implications to Human Resource Management - Basbas, Maria Marietta; David, Divinagracia L.; Gaza, Joy San Buenaventura (Journal of Public Health Sciences, 2024)
Inarguable, being in the workforce is one of the most essential aspects of life.  In fact, the greatest quantity of the lifetime of the people is spent working.  However, the pandemic creates long-lasting effects on the workforce. The pandemic has triggered many modifications reshaping the workforce. There was the abrupt digital and remote working transformation which led to employees a harsh need to quickly adapt to these transformations. With this, there is the big question, how are the employees during this pandemic? How is the well-being of this workforce? This study determined the employees’ well-being of the employees of the University of Nueva Caceres during the COVID-19 pandemic. There were 170 employees of the university who completed the survey administered through online platform. The Personal Wellness Assessment with 8 Dimensions of Wellness was used to measure the well-being of the employees. The Statistical Package for the Social Sciences (SPSS) was used to analyze the data gathered. The results showed that during the COVID-19 pandemic the UNC employees reported high level of well-being. Specifically, they have extremely high spiritual, intellectual, and social but they feel challenged when it comes to emotional, financial, and physical aspects of their well-being. Significant relationships were also found between the age of the employees and their well-being in terms of physical, emotional, and spiritual. Significant relationships were also found between the length of service of the employees and their physical and emotional well-being. The gender differences of the employees along the aspects of well-being were significantly found in social and spiritual. Significant difference in civil status was also found in physical and emotional well-being. The results further indicated no statistical difference in the status of well-being according to the department.